PENGARUH EKOSISTEM HUTAN MANGROVE TERHADAP PRODUKSI PERIKANAN TANGKAP (STUDI KASUS DI KABUPATEN PASURUAN, JAWA TIMUR) - Nuddin Harahab (Jurnal Perikanan Universitas Gadjah Mada, 2009)
Coastal reasorces as mangrove has high supporting effort as water organisms life. The existence of mangrove will give beneficial effect for fish catching productivity in their area. The aims of this research were to obtain informations of fish catching development, and correlation between mangrove ecosystem and fish catching productivity. This reasearch were used descriptive method based on regression and correlation analysis. Any kinds of data that were used in this research were primary data on observation and interview, also secondary data of fish catching productivity and mangrove area from Marine and Fisheries Department, Forestry, and Body of Environmental Management, Pasuruan. The result showed that fish catching productivity in Pasuruan over 15 year period has a slight increase or almost at level off. Then, it showed that mangrove area has significant effect and closely related with shrimps and shells productivity.